THE EFFECT OF SELF - LEADERSHIP, ORGANIZATIONAL CULTURE, AND WORK MOTIVATION ON JOB SATISFACTION AT REGIONAL GENERAL HOSPITAL KARAWANG - Darojat, Tubagus Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to obtain information and to suggest improvement related to the effect of self-leadership,organizational culture, and work motivation on job satisfaction at the Karawang Regional General Hospital. Survey was conducted in this research with 108 samples selected randomly. Data have been analyzed by path analysis. The findings of this research show that (1) self-leadership effects directly on work motivation (2) organizational culture effects directly on work motivation and (3) work motivation effects directly on job satisfaction (4) self-leadership effects directly on work motivation; and (5) organizational culture effects directly on job motivation. Based on those findings it can be concluded that any concern toward self-leadership, organizational culture, work motivation should be put into strategic planning of human resources development in increasing job satisfaction at The Karawang Regional Gereral Hospital.